ANALISIS WACANA KRITIS: DIMENSI SOSIAL DALAM NOVEL TENTANG KAMU KARYA TERE LIYE - Gita Widia; Salsabila; Fitriani Lubis (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This study aims to describe Norman Fairclough's social dimensions by using critical discourse analysis procedures. This study used descriptive qualitative method. The data collection technique used was to record the data found from observations of discourse in the novel. About you by Tere Liye. The data that has been collected is then analyzed using the socially practical steps of the Fairclough critical discourse analysis method. The results and discussion in social practice are divided into three stages, namely situational, institutional and social. There are 31 data in the novel about you by Tere Liye.